Comparative investigation of clinical/radiographical signs of mineral trioxide aggregate and formocresol on pulpotomized primary molars - Shivayogi M Hugar; Shobha D Deshpande (Wolters Kluwer Medknow Publications, 2010)
The objectives of this study were (1) to evaluate clinically and radiographically the effects of mineral trioxide aggregate (MTA) as a pulp dressing after coronal pulp amputation (pulpotomy) in primary molars, (2) to compare the effects of MTA and formocresol in pulpotomized primary teeth. Sixty primary mandibular molars of thirty healthy children aged between 5-8 years were treated by conventional pulpotomy technique. The teeth on the right side are assigned to MTA (Group A) and the left side for the Formocresol (Group B). The children were examined clinically and radiographically every 6 months over a period of 36 months. Results of present study revealed that both MTA and Formocresol has the same effect on the first as well as second primary molars, with chi-square value being 1.1483 (P ≥ 0.05). None of the teeth in either group showed any clinical pathology, showing 100% success rate but radiographically formocresol group showed one case of internal resorption that was regarded as failure in the present study. MTA seems to be more promising predictable with positive response in vital pulp therapy in future than formocresol pulpotomy except for the cost factor.